An investigation of academic dishonesty among undergraduates at Kansas State University - Walton, Candace Lynne Thompson (Kansas State University, 2010)
This study investigated the differences in own behavior and perception of peer behavior among undergraduates among gender, age, race/ethnicity and major. The participants were part of a census of undergraduate students at a Midwestern land grant university. There were 2,759 useable responses to a survey using McCabe’s Academic Integrity Scale. The findings found significant differences between age and gender comparisons. Younger women reported the most behavior in academic dishonesty, and older women reported the lowest behavior in academic dishonesty. The race/ethnicity and major comparisons yielded no differences. Finally, the findings suggest the need for further systematic research on academic dishonesty.
Keywords: academic honesty; cheating; academic integrity; honor code; race ethnicity; gender; Education, Higher (0745)